Effect of particle size and high-energy ball milling time on microstructure and mechanical properties of WC-10Co cemented carbides with plate-like WC grains. (21st August 2019) - Wen, Yan; Liao, Jiaxi; Yang, Qiumin; Yu, Shusheng; Li, Jinzhong; Chen, Liyong; Guo, Shengda; Chen, Hao
Abstract: The effect of particle size and high-energy ball milling time on microstructure and mechanical properties of WC-10Co cemented carbides with plate-like WC grains were studied using a scanning electron microscope, x-ray diffraction and mechanical properties tests. The results show that coarsening W particle size seemed to be beneficial for the increase of the plate-like WC content due to the easy acquirement of the thin W flake with high-density defects. Additionally, increasing the ball milling time could first increase the content of plate-like WC grains, and then decrease with 96 h ball milling. The high amount of defects and activity of fine W particles from fracturing with long ball milling time could enhance the formation of plate-like WC grains. However, the oxygen content could be increased with the excess ball milling time, which reduced the content of liquid Co and thus impeded the formation of plate-like WC grains. As the content of plate-like WC grains increased, the intergranular fracture gradually transformed into the main fracture mode. Additionally, crack bridging and crack path deflection could be seen in the alloy with plate-like WC grains. The high fracture surface area and energy required for crack propagation could improve the strength of WC-10Co cemented carbides with plate-like WC.